Hubungan Kemandirian Lansia Dalam Activity of Daily Living Terhadap Kualitas Hidup Lansia - Lia nurlianawati (Jurnal Keperawatan BSI, 2021)
The Elderly is the last stage of development in the process of human life starting from babies, children, adults and eventually becoming old. In the elderly, there will be various changes and there will be a decrease in physical conditions, namely immobilization, severe senility (dementia), unbearable urination or bowel movements (incontinence), insufficient food and drink intake. The problem in the elderly requires the elderly to adjust themselves continuously, and if the adjustment process is not successful it will be the cause the elderly to become dependent on others and unable to carry out activities independently. Independence is the freedom to act, independent of others, and free to regulate oneself or one's activities, both individually and in groups. Independence is influenced by individual physical, psychological, and environmental factors that can affect the quality of life. The purpose of this study was to determine the relationship between the level of independence of the elderly and the quality of life of the elderly. The research method uses a correlational cross-sectional approach. The population and sample in this study were the elderly in the Budi Pertiwi Nursing Home. The research instrument used the Barthel index for the level of independence and WHOQOL BREFF for quality of life. health status or value of humans as God's creatures who are equipped with thoughts, feelings, determination, rights, and basic human obligations to reach a respectable position in the eyes of humans and Allah SWT. Results of the initial study, the number of elderly people in the nursing home was 35 people, when the study obtained data related to their physical and psychological conditions, some of the elderly suffered from chronic diseases consisting of diabetes, gastritis, hypertension and rheumatism and psychological problems, most of the elderly experienced loneliness because they did not have activities in their spare time that are only spent daydreaming alone, the adaptation of new habits in the midst of the Covid 19 pandemic has created a limitation of social activity for the elderly so that many elderly people do not do activities and activities in their spare time which eventually make the elderly feel lonely, to continue to hone their potential for the elderly and improving the health of the elderly, it is very necessary to implement activities / activities for the elderly during the adaptation of new habits in the midst of the Covid 19 pandemic in the form of implementing activities that can be done in their spare time by the elderly to improve the health, welfare and quality of life of the elderly.